Criminal protection of the right to confidentiality of private communications between Algerian law and French law - Benlecheheb, Asma (Journal of Human Sciences, 2021)
The right to confidentiality of private communications is one of the most important aspects of individuals’ right to privacy. Taking into account the subsequent technical development of wiretapping and recording devices, and the threat this poses to the right to confidentiality of private communications, the constitutional protection established for this right has been extended to the Criminal Code by criminalizing violations of calls of a private or secret nature, regardless of where they are made. However, the use by criminals of the means of communication to commit serious crimes has led the legislator to grant public authorities the right to intercept the secrecy of telecommunications as a method of private investigation in order to reveal the truth. In order to strike a balance between the private interest of individuals and the public interest, the legislator has established a set of procedural controls which must be observed when practicing the interception